Utilization of curcumine and nanocurcumine compounds in cancer therapy - Vajiheh Alinezhad; Heshmatollah Alinezhad; Ramin Ataee; Amin Ataie (Mazandaran University of Medical Sciences, 2017)
Curcumin is a polyphenol extracted from the Curcuma plant. Curcumin has been used widely in ayurvedic medicine for centuries; it has a variety of biological properties including anti-oxidant, analgesic, anti-inflammatory and antiseptic activity. Curcumin has shown anti-cancer activities through variety of biological pathways engaged in mutagenesis, oncogene expression, cell cycle regulation, apoptosis, tumorigenesis and metastasis. Curcumin has proved anti-proliferative effect in many cancers, and is an inhibitor of the transcription factor NF-κB and downstream gene products (including c-myc, Bcl-2, COX-2, NOS, Cyclin D1, TNF-α, interleukins and MMP-9). Furthermore, curcumin affects a variety of growth factor receptors and cell adhesion molecules involved in tumor growth, angiogenesis and metastasis. However, a limiting factor is its extremely low bioavailability which hinders its use as therapeutic agent. Therefore, many technologies have been developed to overcome this limitation. We summarize to develop curcumin delivery aims and increase solubility for improving curcumin bioavailability and anticancer potential for therapy.